Piecewise-Quadratic Walsh’s Bases Algorithms of Calculation of Medical Signals - Rakhimov Bakhtiyar Saidovich; Allaberganova Sevara Ibragim Qizi; Ibodullaeva Zarnigor Ollayor Qizi; Saidov Atabek Bakhtiyarovich (International Journal on Orange Technologies, 2022)
In work the examples of analytically set and experimentally received dependences advantages of the developed algorithm of spectral transformation in basis of piecewise-quadratic Walsh’s functions are shown. The offered system and algorithm on its basis can find wide applications in such areas, as computer graphic, images processing and restoration, machine vision and multimedia, animation and manufactures of computer games.